The Emerging Role of Sharia Compliance to Enhance Public Trust in Islamic Cooperatives with Good Cooperative Governance as a Mediating Factor - Rahmat, Biki Zulfikri; Ramadhani, Indi; Zahra, Qiny Shonia Az (UPT Publikasi Ilmiah UNISBA, 2025)
This research examines the role of sharia compliance and label in enhancing public trust in sharia cooperatives in Tasikmalaya, with Good Cooperative Governance (GCG) acting as a mediating factor. Employing a quantitative approach, data were collected through surveys distributed to cooperative members and analyzed using regression analysis of mediating variables (product of coefficient method). The findings reveal that sharia compliance and sharia label alone is insufficient to build trust; rather, strong governance mechanisms play a crucial role in reinforcing public trust. The mediation analysis confirms that GCG significantly strengthens the relationship between sharia compliance and trust and also between sharia label and trust, highlighting the need for cooperative managers to integrate governance best practices with Islamic financial principles. The study contributes to the literature on Islamic microfinance by demonstrating the critical function of governance in trust-building and offers practical recommendations for cooperative leaders to enhance sustainability. Future research should explore qualitative insights into member perceptions and expand the study to other regions to improve generalizability.